Pregnancy Outcomes and Blood Pressure Visit-to-Visit Variability and Level in Three Less-Developed Countries. Issue 5 (29th March 2021) - Magee, Laura A.; Bone, Jeffrey; Owasil, Salwa Banoo; Singer, Joel; Lee, Terry; Bellad, Mrutunjaya B.; Goudar, Shivaprasad S; Logan, Alexander G.; Macuacua, Salésio E.; Mallapur, Ashalata A.; Nathan, Hannah L.; Qureshi, Rahat N.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : In pregnancy in well-resourced settings, limited data suggest that higher blood pressure (BP) visit-to-visit variability may be associated with adverse pregnancy outcomes. Included were pregnant women in 22 intervention clusters of the CLIP (Community-Level Interventions for Preeclampsia) cluster randomized trials, who had received at least 2 prenatal contacts from a community health worker, including standardized BP measurement. Mixed-effects adjusted logistic regression assessed relationships between pregnancy outcomes and both BP level (median [interquartile range]) and visit-to-visit variability (SD and average real variability [ARV], adjusted for BP level), among all women and those who became hypertensive. The primary outcome was the CLIP composite of maternal and perinatal mortality and morbidity. Among 17 770 pregnancies, higher systolic and diastolic BP levels were associated with increased odds of the composite outcome per 5 mm Hg increase in BP (odds ratio [OR], 1.05 [95% CI, 1.03–1.07] and OR, 1.08 [1.06–1.11], respectively). Higher BP visit-to-visit variability was associated with increased odds, per a SD increase in BP variability measure, of (1) hypertension (systolic: OR, 2.09 [1.98–2.21] for SD and 1.52 [1.45–1.60] for ARV; diastolic: OR, 2.70 [2.54–2.87] for SD and 1.86 [1.76–1.96] for ARV); and (2) the composite outcome (systolic: OR, 1.10 [1.06–1.14] for SD and 1.06 [1.02–1.10] for ARV; diastolic: OR, 1.07 [1.03–1.11] for SD and 1.06 [1.02–1.09] for ARV). In 3 less-developed countries, higher BP level and visit-to-visit variability predicted adverse pregnancy outcomes, providing an opportunity for high-definition medicine.